Clinical Changes in Older Adults During Hospitalization: Responsiveness of the interRAI Acute Care Instrument. Issue 5 (16th April 2013) - Wellens, Nathalie I. H.; Verbeke, Geert; Flamaing, Johan; Moons, Philip; Boonen, Steven; Tournoy, Jos; Milisen, Koen
<x xml:space="preserve">Abstract</x> Objectives To evaluate the responsiveness of the Minimum Data Set interRAI Acute Care (AC), a comprehensive geriatric assessment system, to detect clinical changes in patient status during hospital stays. Design An explorative secondary data‐analysis comparing prospectively collected data with the interRAI AC before hospitalization, upon admission, and at discharge. Setting Clinicians from multiple disciplines in nine geriatric and eight nongeriatric wards of nine acute hospitals performed the assessment. Participants The interRAI AC was administered serially to 256 geriatric inpatients (aged 83.2 ± 5.2; 60% female). Measurements Responsiveness (capacity to detect changes in patients) was calculated for the output scales on five domains: activities of daily living (ADLs), cognition, communication, depressive symptoms, and pain. Internal responsiveness was evaluated using the Friedman test and Guyatt technique. Results Significant differences in clinical status were found for all five domains, based on the Friedman test. Post hoc tests revealed differences between each assessment period, except for cognition and communication from admission to discharge and for depressive symptoms from before admission to discharge. The Guyatt Responsiveness Index showed good to excellent capacity to detect longitudinal changes during hospitalization for cognition, communication, and pain and substantial performance for ADLs and depressive symptoms. Conclusion In older inpatients, fluctuations in ADLs, cognition, communication, depressive symptoms, and pain can be captured using the interRAI AC output scales, enabling clinicians to evaluate longitudinal changes from admission to discharge and to provide a comparison with patient status before the acute onset of the illness. These results support the use of these scales in geriatric and nongeriatric wards.